Arcuatitibia kerzhneri, a new genus and species of Reduviinae (Hemiptera: Reduviinae) from China - Luo, Zhaohui; Lu, Zhaozhi; Cai, Wanzhi (Zootaxa, 2009)
A new genus, Arcuatitibia Luo, Lu & Cai, and one new species, A. kerzhneri Luo, Lu & Cai, are described in the subfamily Reduviinae, based on the materials from Xinjiang, China. The dorsal habitus, male genitalia, and other diagnostic morphological features are illustrated.